2021
DOI: 10.1021/acs.iecr.0c05979
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Selective Adsorption of Neodymium on Expanded Vermiculite

Abstract: In this study, expanded vermiculite (EV) was applied to the adsorption of neodymium (Nd) from an aqueous solution with focus on the description of the kinetics and the mechanism of adsorption, determination of the best eluent, and selectivity. The EV was characterized before and after the adsorption process by the morphology, composition, textural properties (specific surface area, density, and porosity), and functional groups. The adsorption experiments showed that under optimal conditions, using 0.7 g of ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Figure presents the FTIR spectra of the spent material that shows peaks referring to interlamellar water, 3400 and 1630 cm –1 , OH stretching and bending vibrations, respectively, and bands located in the 1300–500 cm –1 range that reveal structural characteristics of clay minerals. , The silicate characteristic bands are found at 999.5 cm –1 , representing Si–O’s stretching vibrations, at 745 cm –1 , indicating the Si–O–Si (Al) stretching, and at lower frequencies 522 and 459 cm –1 , meaning Si–O bending . At 675 cm –1 , the characteristic stretching vibration of the interlayer metal bond (M–O) indicates that magnesium, the exchangeable cation of this expanded vermiculite, replaced dysprosium in the interlayer spaces maintaining the original vibrational characteristic of the M–O bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure presents the FTIR spectra of the spent material that shows peaks referring to interlamellar water, 3400 and 1630 cm –1 , OH stretching and bending vibrations, respectively, and bands located in the 1300–500 cm –1 range that reveal structural characteristics of clay minerals. , The silicate characteristic bands are found at 999.5 cm –1 , representing Si–O’s stretching vibrations, at 745 cm –1 , indicating the Si–O–Si (Al) stretching, and at lower frequencies 522 and 459 cm –1 , meaning Si–O bending . At 675 cm –1 , the characteristic stretching vibration of the interlayer metal bond (M–O) indicates that magnesium, the exchangeable cation of this expanded vermiculite, replaced dysprosium in the interlayer spaces maintaining the original vibrational characteristic of the M–O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Expanded vermiculite, a hydrated silicate magnesium, aluminum, and iron, is the adsorbent material employed in the column. It was characterized in previous studies, , which showed some physical–chemical properties such as an interlayer space of 14.1 Å, a layered structure with a surface area of 9.88 m 2 /g, and an elemental composition of Mg (15.7%), Al (7.63%), Si (21.8%), Fe (7.49%), O (45.9%), and trace elements (1.48%). In this study, the material was analyzed after five cycles of reuse.…”
Section: Methodsmentioning
confidence: 99%
“…These results are in accordance with those (20.6 U ml −1 ) obtained by Karanam et al [44] in the hydrolysis of p-nitrophenyl palmitate (pNPP) by a lipase preparation using a genetically modified strain of A. japonicus MTCC 1975. Evaluating the lipase production by A. japonicus LAB01 in medium supplemented with sunflower oil (1% w w −1 ), at pH 6.0, Souza et al [47] achieved 28.04 U ml −1 on pNPP hydrolysis. Likewise, purified lipase obtained by A. japonicus produced in cultivation media containing malt extract, also showed specific activity of 36.83 U mg −1 , using Jatropha oil as substrate [45].…”
Section: Production Of Lipase By a Japonicusmentioning
confidence: 99%
“…Inorganic clays are low-cost supports, with high adsorption capacity, environmentally friendly properties and renewable abundance [18,19]. Among those, clay minerals such as, diatomite, vermiculite, montmorillonite KSF and kaolinite are good examples of supports for enzyme immobilization [20], due to the unique physicochemical characteristics, viz, high thermal and chemical stability, mechanical strength, charge density (excellent ion exchange and adsorption capacity), relative hydrophobicity-hydrophilicity, high surface area, microbial resistance, environmental sustainability and economically viable [18,[21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Among the natural adsorbents, different types of natural clay are attracting attention, for their non-toxicity, stability, low-cost and abundance [32]. Kaolinite [33,34], montmorillonite [35,36], vermiculite [37] and bentonite [38][39] are some of the natural clays which were used as adsorbents for the separation and detection of different metal ions. In the literature, it was reported that chamotte clay was used for the palm kernel biodiesel purification [40] and adsorption of lead(II) [41].…”
Section: Introductionmentioning
confidence: 99%